In-vitro and in-vivo comparative effects of the spring and autumn-harvested Artemisia aucheri Bioss extracts on Leishmania major. (15th July 2020) - KarimiPourSaryazdi, Amir; Ghaffarifar, Fatemeh; Dalimi, Abdolhossein; Dayer, Mohammad Saaid
Abstract: Ethnopharmacological relevance: Artemisia aucheri Bioss contains flavonoid, coumarin and santonin with antioxidant, antimicrobial and antileishmanial effects. The current study was aimed to comparatively evaluate the effects of spring and autumn extracts of A. aucheri Bioss on Leishmania major both in-vitro and in-vivo conditions. Methods: HPLC analysis was used to evaluate the percentages of compounds in spring and autumn extracts of A. aucheri . For in-vitro assay, the effect of different concentrations of spring and autumn extracts of A. aucheri was tested on L. major promastigotes and amastigotes. MTT and flow cytometry methods were used to evaluate the cytotoxicity and probable apoptosis of A. aucheri extracts on L. major promastigotes. On the other hand, for in-vivo assay, the extracts were used as ointments to treat lesions developed on BALB/c mice after 28 days post inoculation of L. major . The diameter of lesions and the survival rates of infected BALB/c mice were measured weekly for a period of two months. Results: The HPLC analysis showed the substance Quercitrin was present in the spring A. aucheri extract but not in the autumn extract. The mean numbers of amastigotes in each treated macrophage with the spring and autumn A. aucheri extracts were 1.2 and 1.8 respectively, which showed statistically significant differences (P < 0.05). Flow cytometry revealed that the spring and autumn A. aucheri extracts caused about 32% and 3.78% apoptosis respectively. The inhibitory concentration (IC50) of spring and autumn A. aucheri extracts to amastigotes were determined to be 90 μg/mL and 183 μg/mL respectiovely. In-vivo, the diameter of lesions treated with the spring A. aucheri extract was significantly less (P < 0.05) compared to those treated with the autumn extract (2.6 and 7.8 mm respectively). Also, mice treated with spring A. aucheri extract had higher survival rates compared to control group. Conclusion: Given the above results, it can be concluded that spring A. aucheri extract has a greater fatality effect on L. major promastigotes in-vitro compared to the autum extract. In addition, the spring extract has stronger therapeutic effect on lesions caused by L. major in BALB/c mice than the autum extract. Graphical abstract: Image 1 Highlights: spring A.aucheri extract compared to autumn A.aucheri extract had a greater fatality effect on L. major promastigotes and amastigotes. Spring A.aucheri extract induced more apoptosis. The results of in vivo showed that A.aucheri spring extract compared to A.aucheri autumn extract led to further wound healing.